Interaksi Komunikasi Orang Tua Dan Anak Dalam Membentuk Perilaku Positif Di Kelurahan Mabar Hilir Kota Medan - Jihan Tiara Afifah; Hasan Sazali; Sori Monang (Jurnal Sains Sosio Humaniora, 2022)
This research has the title Parent-Child Communication Interaction in Forming Positive Behavior in Mabar Hilir Village. The purpose of this analysis is to find out the relationship between interpersonal communication between parents and children and to find out the description of the role of interpersonal communication in children when forming positive behavior in Mabar Hilir Village. From this analysis it is shown where (I) the behavior of children will be influenced by good communication from parents to children, therefore it is important for parents to find out how to communicate with children. (2) by prioritizing the interests of children and the relationship between parents and children that must be reciprocal, it will make parent-child communication interpersonal, the role of parents here is also important in supervising children who live in the community who can get external influences so that they affect behavior child.